2017
DOI: 10.1111/jrh.12258
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Substance Use Care Among Young Adults Before and After Affordable Care Act (ACA) Implementation: A Rural and Urban Comparison

Abstract: Although rates of insurance increased for all young adults, a significant rural/urban difference persisted in 2014. Meaningful increases in MH and AOD treatment may require targeted efforts to reduce noninsurance barriers to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Though this study was small and qualitative, perceptions and experiences reported by providers are supported by larger studies that have documented geographic differences in access to and utilization of specialty care, including care for substance use disorders . Research has shown that patients who receive primary care services in rural clinics have fewer specialty care encounters in general and significantly lower odds of specialty, mental health, and ancillary visits compared to patients seen in primary care clinics in urban areas .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Though this study was small and qualitative, perceptions and experiences reported by providers are supported by larger studies that have documented geographic differences in access to and utilization of specialty care, including care for substance use disorders . Research has shown that patients who receive primary care services in rural clinics have fewer specialty care encounters in general and significantly lower odds of specialty, mental health, and ancillary visits compared to patients seen in primary care clinics in urban areas .…”
Section: Discussionmentioning
confidence: 70%
“…Though this study was small and qualitative, perceptions and experiences reported by providers are supported by larger studies that have documented geographic differences in access to and utilization of specialty care, including care for substance use disorders. 28,33,35,[51][52][53] Research has shown that patients who receive primary care services in rural clinics have fewer specialty care encounters in general and significantly lower odds of specialty, mental health, and ancillary visits compared to patients seen in primary care clinics in urban areas. 28,33,53 Studies have also described multiple barriers to accessing substance use treatment in rural settings, including limited availability of treatment services, insufficient funding, transportation barriers, stigma-related barriers, and a lack of interagency collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the US financing and delivery system due to the Affordable Care Act (ACA) insurance expansion and delivery system changes and innovations have differentially impacted rural areas. Understanding differences in referral patterns between rural and urban areas over time is important.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ACA called for a redesign of PC with a focus on the integration of physical and mental health services under patient-centered medical homes and accountable care organization reforms [ 46 , 47 , 48 ]. The few published investigations into mental health services use around the time of the ACA have not specifically examined PC-provided mental health services [ 9 , 49 , 50 , 51 ]. Moreover, limited research in this area has not accounted for heterogeneity within the Latino population with respect to both US versus foreign/island nativity and country of origin which, based on analyses of Black populations in the National Survey of American Life, can differ by nativity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%